THE IMPACT OF DIGITAL SOLUTIONS ON THE STABILITY OF THE BANKING SYSTEM: EMPIRICAL EVIDENCE FROM UZBEKISTAN (Academicia Globe: Inderscience Research, 2025)
The article is devoted to analyzing the impact of digital solutions on the stability of Uzbekistan's banking system. It explores institutional and technological aspects of digitalization, and its relationship with key indicators of financial stability—capital adequacy (CAR) and non-performing loans (NPL). Based on reports from the Central Bank, McKinsey, Accenture, and other international organizations, the study conducts an empirical analysis of digital transformations. The conclusion highlights the positive effect of digital solutions on stability, especially in the context of regional digital inequality and regulatory challenges.